Role of miRNAs and their potential to be useful as diagnostic and prognostic biomarkers in gastric cancer - da Silva Oliveira, Kelly Cristina (2016)
Alterations in epigenetic control of gene expression play an important role in many diseases, including gastric cancer. Many studies have identified a large number of upregulated oncogenic miRNAs and downregulated tumour-suppressor miRNAs in this type of cancer. In this review, we provide an overview of the role of miRNAs, pointing to their potential to be useful as diagnostic and/or prognostic biomarkers in gastric cancer. Moreover, we discuss the influence of polymorphisms and epigenetic modifications on miRNA activity.